2020
DOI: 10.1177/1708538120932713
|View full text |Cite
|
Sign up to set email alerts
|

Atherectomy with balloon angioplasty compared to balloon angioplasty alone for the treatment of chronic limb threatening ischemia: A national surgical quality improvement program database analysis

Abstract: Objectives To compare perioperative outcomes related to atherectomy with percutaneous transluminal angioplasty versus percutaneous transluminal angioplasty alone for the treatment of lower extremity chronic limb threatening ischemia using a national patient database. Methods Patients with chronic limb threatening ischemia treated with atherectomy and percutaneous transluminal angioplasty or percutaneous transluminal angioplasty alone from 2011 to 2016 in the National Surgical Quality Improvement Program databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There were total 9 studies; 4 RCTs 7-10 and 5 retrospective observational studies [11][12][13][14][15] that met the inclusion criteria. The study by Lam et al 16 was excluded because it reports only 30-day outcomes. The pertinent details of the included trials and the study characteristics are shown in Table 1.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…There were total 9 studies; 4 RCTs 7-10 and 5 retrospective observational studies [11][12][13][14][15] that met the inclusion criteria. The study by Lam et al 16 was excluded because it reports only 30-day outcomes. The pertinent details of the included trials and the study characteristics are shown in Table 1.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Stenotic cardiovascular diseases, in particular, atherosclerosis, are the leading cause of morbidity and mortality worldwide despite improvements in medical therapies [1]. Currently, two major clinical approaches are used to resume obstructed blood flow: angioplasty and bypass surgery [2,3]. Unfortunately, following either procedure, neointimal hyperplasia (IH) develops in the vessel wall, and if untreated, could narrow the vessel lumen and contribute to recurrent stenosis or bypass graft failure.…”
Section: Introductionmentioning
confidence: 99%